Achievements and trends of solid oxide fuel cells in clean energy field: a perspective review - Abdalla, A.M. (Higher Education Press, 2018)
The main concerns in the world today, especially in the energy field, are subjected to clean, efficient, and durable sources of energy. These three aspects are the main goals that scientist are paying attention to. However, the various types of energy resources include fossil and sustainable ones, but still some challenges are chasing these kinds from energy conversion, storage, and efficiency. Hence, the most reliable and considered energy resource nowadays is the utilized one which is as highly efficient, clean, and everlasting as possible. So, in this review, an attempt is made to highlight one of the promising types as a clean and efficient energy resource. Solid oxide fuel cell (SOFC) is the most efficient type of the fuel cell types involved with hydrogen and hydrocarbon-based fuels, especially when it works with combined heat and power (CHP). The importance of this type is due to its nature of work as conversion tool from chemical to electrical for generation of power without noise, pollution, and can be safely handled. Â© 2018 Higher Education Press and Springer-Verlag GmbH Germany, part of Springer Nature